Spatially resolved acoustic spectroscopy (SRAS) technology development - Coulson, Jethro (2016)
In this thesis the progress made in developing the spatially resolved acoustic spectroscopy (SRAS) technology for industrial deployment is presented. SRAS is a noncontact laser ultrasound materials characterisation instrument which uses surface acoustic waves (SAWs) to image and determine surface microstructure on metallic samples. SRAS offers advantages over existing techniques for determining microstructure, primarily speed, large sample sizes and full sample coverage. The technique is developed in four key areas: instrumentation, signal analysis, machine vision for auto-focus and modelling generation of laser-ultrasound.